The relationship between family conflict resolution methods and depressive symptoms in patients with chronic diseases - Min Jeong Joo; Jisu Ko; Jae Hyeok Lim; Dan Bi Kim; Eun-Cheol Park (PLoS ONE, 2025)
Background Individuals with chronic diseases are more sensitive to depressive symptoms and stress compared to the general population. The complexity and unpredictability of these diseases necessitate family involvement in their management. However, long-term disease can exhaust both patients and their families, leading to conflicts and increased stress, thus exacerbating depressive symptoms. This longitudinal study investigated the impact of family conflict resolution methods on depressive symptoms among chronic disease patients in Korea. Methods We used data from the Korean Welfare Panel Study, collected from 2012 to 2022, analyzing 10,969 chronically ill cohabiting or married individuals. Chi-square tests were used to compare group characteristics, and generalized estimating equation models were used for regression analysis, focusing on Center for Epidemiologic Studies Depression Scale-11 scores, family conflict resolution changes, and covariates. Results Participant groups that changed from positive to negative conflict resolution methods were more likely to have depressive symptoms than the group that did not change from positive methods (positive →  negative odds ratios (OR) =  1.34, confidence intervals (CI) =  1.24–1.44). In addition, participants who did not change from negative methods were significantly more depressed than those who maintained positive methods over time (negative →  negative OR =  1.48, 95% CI =  1.37–1.59). Uncollaborative discussions and domestic violence resolution methods were related to depressive symptoms in family conflict resolution methods. Conclusion Negative family conflict resolution methods influence depressive symptoms in individuals with chronic diseases. Even after transitioning to positive conflict resolution methods, prior negative experiences continued to impact depressive symptoms.